Review of 1971/02/05 Concert at Barber Institute of Fine Arts. University of Birmingham lunchtime piano recital of music by Prokofiev and Debussy, player by Julia Illingworth. - Villars, Chris (Contact: A Journal for Contemporary Music (1971-1990), 1971)